Program Kemitraan Masyarakat bagi Kelompok Kader Kesehatan Ibu Hamil dalam Implementasi Program Pendampingan Kehamilan di Wilayah Puskesmas Arjowinangun Malang - Gita Kostania; Rita Yulifah; Suprapti Suprapti (Poltekkes Kemenkes Surakarta, 2024)
Background: Pregnancy in a woman is a physiological process, but there is a risk of experiencing pregnancy complications. Many influencing factors, both direct and indirect, can cause maternal death. In 2021, pregnancies with risks at the Arjowinangun Community Health Center were 335 (43.96%). One of the programs carried out to overcome maternal mortality is